1991
DOI: 10.1084/jem.174.6.1347
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the motility-related protein (MRP-1), recognized by monoclonal antibody M31-15, which inhibits cell motility.

Abstract: SummaryA murine monodonal antibody (M31-15) was identified using the penetration-inhibiting assay of a human lung adenocarcinoma cell line (MAC10) and remarkably inhibited the phagokinetic tract motility of various cancer cell lines. The antigen, motility-related protein (MRP-1), recognized by M31-15, was 25-and 28-kD proteins, and M31-15 was used to isolate a cDNA clone from a human breast carcinoma cDNA library. Sequence analysis revealed that MRP-1 had strong similarity with a B cell surface antigen (CD37),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
114
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 26 publications
3
114
1
Order By: Relevance
“…One of those factors, cell motility, plays an important role in the progression, especially after the extravasation. Motility-related protein 1 (MRP-1/CD9), which belongs to the transmembrane 4 superfamily of membrane proteins, is considered to inhibit cell motility (Miyake et al, 1991). It has been demonstrated that the cells which expressed MRP-1/CD9 by transfection showed suppressed cell motility in vitro (Ikeyama et al, 1993).…”
mentioning
confidence: 99%
“…One of those factors, cell motility, plays an important role in the progression, especially after the extravasation. Motility-related protein 1 (MRP-1/CD9), which belongs to the transmembrane 4 superfamily of membrane proteins, is considered to inhibit cell motility (Miyake et al, 1991). It has been demonstrated that the cells which expressed MRP-1/CD9 by transfection showed suppressed cell motility in vitro (Ikeyama et al, 1993).…”
mentioning
confidence: 99%
“…5,7,9,10 mAbs directed to the CD9 molecule have also been shown to inhibit the migration of different types of carcinoma tumor cells and the transendothelial migration of melanoma cells. [11][12][13] Therefore, the inverse correlation observed between CD9 expression and the metastatic potential could be explained, at least in part, by the effects mediated by CD9 on cell adhesion and migration through the interactions among this tetraspanin and different integrins. 2,3 We have recently described a functional conformation of CD9, detected by the anti-CD9 mAb PAINS-13, that is imposed upon association of this tetraspanin with members of the beta-1 subfamily of integrins and particularly with a6b1, a cellular adhesion receptor for laminin.…”
mentioning
confidence: 99%
“…The possibility of anti-invasion and anti-motility strategies may have important implications for cancer management. In the past few years, various agents have been shown to possess anti-invasion and anti-metastasis properties; among these are Arg-Gly-Asp (RGD) sequence peptides and motility-regulating factors (Miyake et al, 1991;Mohler et al, 1992;Isoai et al, 1993). Although essential fatty acids have previously been shown to inhibit cancer cell growth after relatively prolonged incubation, the effect of essential fatty acids on cancer cell motility and invasion have not been previously reported.…”
Section: Cell Attachment Assaymentioning
confidence: 87%